Driving Excellence: How School-Based Management, Leadership, and Work Culture Shape Junior High School Teacher Performance in Serang City - Maya Sari Putri; Hamdan Hamdan (International Forum of Researchers and Lecturers, 2025)
This study investigates the simultaneous and individual effects of School-Based Management (SBM), principal supervision, transformational leadership, and work culture on the performance of junior high school teachers in Serang City, Indonesia. Against the backdrop of the Merdeka Curriculum and the shift to hybrid learning in the post-pandemic era, the research addresses persistent challenges such as hierarchical school cultures and technological disparities. Employing a quantitative ex post facto approach, data were collected from 316 teachers across public and private schools through structured questionnaires, classroom observations, and document analysis. Multiple linear regression analysis reveals that SBM, principal supervision, transformational leadership, and work culture each have significant and positive impacts on teacher performance, with transformational leadership and work culture exerting the most substantial influence. The results demonstrate that 74% of the variance in teacher performance can be explained by these four organizational factors, underscoring their critical role in shaping pedagogical competence, classroom management, and professional development. The study further highlights the necessity for comprehensive managerial training, the integration of technology in supervisory practices, and the cultivation of collaborative and innovative work cultures. Practical recommendations include enhancing principal leadership capacity, fostering instructional supervision, and investing in digital infrastructure to support sustainable improvements in teacher performance. The findings contribute to the body of knowledge on educational management in Indonesia and offer actionable insights for policymakers, school leaders, and educators aiming to strengthen teacher effectiveness amidst ongoing educational reforms and digital transformation.